The Osase Information System In Web-Based Operation And Device Monitoring At Pt. Telkom Indonesia Arnet Witel Division Medan - Prawira, Yudhi; Hanum, Latifah; Syaifuddin, Muhammad (Ali Institute or Research and Publication, 2022)
PT.Telkom Indonesia is a State-Owned Enterprise (BUMN) which is engaged in information and communication technology (ICT) services and telecommunications networks in Indonesia. Telkom provides fixed wireline services, fixed wireless telephone services, mobile telephone services, data/internet and other multimedia services. PT.Telkom Indonesia has an information technology-based information system that can support and support employee performance every day. This information technology is a Web-based OSASE Information System. This OSASE information system functions as an early warning against disturbances in the CME (Civil Mechanical Electrical) sub-division system.